Mammalian thioredoxin reductase 1: roles in redox homoeostasis and characterization of cellular targets - Turanov, Anton A. (2010)
The classical Trx (thioredoxin) system, composed of TR (Trx reductase), Trx and NADPH, defines a major pathway of cellular thiol-based redox regulation. Three TRs have been identified in mammals: (i) cytosolic TR1, (ii) mitochondrial TR3 and (iii) testes-specific TGR (Trx-glutathione reductase). All three are selenocysteine-containing enzymes with broad substrate specificity in in vitro assays, but which protein substrates are targeted by TRs in vivo is not well understood. In the present study, we used a mechanism-based approach to characterize the molecular targets of TR1. Cytosolic Trx1 was the major target identified in rat and mouse liver, as well as in rat brain and mouse serum. The results suggest that the main function of TR1 is to reduce Trx1. We also found that TR1-based affinity resins provide a convenient tool for specific isolation of Trxs from a variety of biological samples. To better assess the role of TRs in redox homoeostasis, we comparatively analysed TR1- and TR3-knockdown cells. Although cells deficient in TR1 were particularly sensitive to diamide, TR3-knockdown cells were more sensitive to hydrogen peroxide. To further examine the TR1–Trx1 redox pair, we used mice with a liver-specific knockout of selenocysteine tRNA. In this model, selenocysteine insertion into TR1 was blocked, but the truncated form of this protein was not detected. Instead, TR1 and TR3 levels were decreased in the knockout samples. Diminished hepatic TR1 function was associated with elevated Trx1 levels, but this protein was mostly in the oxidized state. Overall, this study provides evidence for the key role of the TR1–Trx1 pair in redox homoeostasis.